Efficacy of cyclin-dependent kinases 4 and 6 inhibitors in the treatment of HR +/HER2 − advanced breast cancer: a meta-analysis - Isah Adamu Danbala; Xu Wang; Yuting Su; Haowen Tang; Wanying Sheng; Zakari Shaibu; Iliyasu Isah; Xiao Yuan (European Journal of Medical Research)
Abstract Aim This study investigates the efficacy and safety of cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) combined with endocrine therapy (ET) in treating hormone receptor-positive (HR +), human epidermal growth factor receptor 2-negative (HER2-) advanced breast cancer. Methods A systematic review of randomized clinical trials (RCTs) from 2015 to 2024 was conducted using databases such as PubMed, Google Scholar, Embase, and Cochrane. Data were collected on treatment outcomes, including complete response (CR), partial response (PR), stable disease (SD), progressive disease (PD), overall response rate (ORR), and treatment-related adverse events (TRAEs). Analysis was performed using Review Manager 5.4.1, following PRISMA guidelines, with registration in the PROSPERO database (ID: CRD42023471168). Results 1223 studies screened, 13 met inclusion criteria. CDK4/6i + ET significantly reduced PD rates and increased SD compared to ET + chemotherapy. No significant differences were observed in CR, PR, or SD between the groups. CDK4/6i + ET demonstrated a favorable safety profile with fewer high-grade TRAEs but had a higher incidence of grade 3–4 adverse events than ET alone. Conclusion CDK4/6i combined with ET improves disease control by decreasing progression and increasing stability, though it shows a lower PR rate than ET + chemotherapy in HR + /HER2 − advanced breast cancer. These findings underscore the need to balance efficacy with tolerability when selecting treatment strategies.